2005
DOI: 10.1111/j.1365-2929.2005.02314.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of text and video cases in a postgraduate problem-based learning format

Abstract: The greater improvement in clause frequency after the video case compared with the equivalent text suggests an improvement in data exploration, theory building and theory evaluation. The use of patient video recordings may be a valuable supplement to postgraduate paediatric training, particularly pertaining to movement disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
3
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 12 publications
4
81
3
3
Order By: Relevance
“…Hence, we know little about the cognitive processes that occur when learners collaboratively analyse video or paper patient cases. Our previous study of verbal interaction in a group of paediatric residents showed that a PVC induced cognitive processes that were superior to those triggered by paper cases (Balslev et al 2005). However, the analysis of the cognitive processes in this study was restricted to the recorded verbal interactions in the group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, we know little about the cognitive processes that occur when learners collaboratively analyse video or paper patient cases. Our previous study of verbal interaction in a group of paediatric residents showed that a PVC induced cognitive processes that were superior to those triggered by paper cases (Balslev et al 2005). However, the analysis of the cognitive processes in this study was restricted to the recorded verbal interactions in the group.…”
Section: Introductionmentioning
confidence: 99%
“…Both groups analysed the same written vignette of the case and formulated learning objectives after the analysis (Balslev et al 2005). Next, group B was shown a brief (2.5 min) video of the patient in the vignette, whilst group A read a written description of the video without actually watching it.…”
Section: Group Sessionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Segments of the PBL case are presented via video to provide students with practice in listening to the patient's story or to engage them emotionally with the patient's experience of illness. The video can introduce students to other family members, demonstrate patient/physician interactions, or give a voice to patients' concerns (Balslev et al 2005). Web-based, video-rich cases such as those produced by L.I.V.E.…”
Section: Pbl Innovationsmentioning
confidence: 98%
“…Moreover, the combination of visual clues within an effective and systematic exploitation of well-selected video sequences can help increase students' interest and serve as a stimulus for free discussion in group work (Bouthillier & Dilanni, 2001). When compared with the equivalent text, a video presentation has been shown to be particularly helpful for medical postgraduates working within a PBL learning format (Balslev, de Grave, Muijtjens & Scherpbier, 2005). The video mediated experience resulted in an improvement in data exploration, theory building and theory evaluation.…”
Section: Attributes Of Video Technologymentioning
confidence: 99%